The effect of Changes in the Injection Parameters of Oily Solid Waste on Environment Pollution. (Jurnal Kajian Lingkungan, 2013)
Waste disposal is one of the many environmental issues becoming increasingly difficult to deal with. A single disposal well may not be sufficient to handle the large volume of water and solid wastes generated as a product from the oil production. Up to 700-800 m3/day of solid waste and braine water are generated from five oil production Central Gathering Stations (CGS) in the Duri oilfield. This thesis discusses âThe effect of Changes in the Injection Parameters of Oily Solid Waste on Environment Pollutionâ. The research purpose is to know the relationship between surface injection parameters such as waste density, injection rate, waste slurry concentration and viscosity of bottom-hole pressure. The oily solid waste is injected back into target formation with criteria such as high permeability, good porosity and poor consolidated sand. The formation around the wellbore begins to fill with the injected waste material then the water component of the slurry dissipates into the formation. The bottom-hole pressure response is one of environment pollution indicator during waste injection. Based on result of multi linier regression analysis showed slight positive and negative effect on surface parameter of the bottom-hole pressure although not significant. Result of groundwater monitoring analysis (pH, boron, zinc, TPH, temperature and Sodium) from two monitoring wells did not show any changes in groundwater quality before and after the injection period so that not environmental pollution.Keyword :injection, pollution, oily solid waste, environment